Importance of patient reported outcome measures versus clinical outcomes for breast cancer patients evaluation on quality of care. (June 2016) - Kool, Melissa; van der Sijp, Joost R.M.; Kroep, Judith R.; Liefers, Gerrit-Jan; Jannink, Ilse; Guicherit, Onno R.; Vree, Robbert; Bastiaannet, Esther; van de Velde, Cornelis J.H.; Marang – van de Mheen, Perla J.
Abstract: Introduction: Given increasing numbers of breast cancer survivors, there is an increased focus on quality of life and quality of care. This study aims to investigate whether clinical or patient reported outcomes are most important for perceived quality of care by breast cancer patients. Methods: Overall, 606 patients aged 18 years or older, who underwent breast cancer surgery 9–18 months ago in five hospitals in the Netherlands, were invited to complete an internet-based questionnaire. Patients were asked to judge a random selection of 24 patient profiles and choose which of 2 presented patients had received the best quality of care, using conjoint analysis. The individual relative importance (RI) for each outcome was estimated using Hierarchical Bayes Estimation, and averaged over all patients to assess which outcomes were most important. Results: Complete data were available for 350 patients (58%). Avoiding severe breast symptoms was most important for good quality of care according to patients (RI 23.22 [95% Confidence Interval (95% CI) 22.32–24.12]), followed by a 2 year longer disease free survival (18.30 [17.38–19.22]). However, the importance differed by age: younger patients (<50 years) assigned higher importance to longer disease free survival (21.99 [19.52–24.46]) than older patients (65 + years) (15.03 [13.88–16.18]). Conclusion: Avoiding severe breast symptoms rather than 2 year longer disease free survival is considered most important in our population of breast cancer patients for evaluation of quality of care. These data should thus be included in both information provision prior to treatment choices and post treatment quality of care evaluation. Highlights: Avoiding severe breast symptoms were most important for perceived quality of care. Patients would exchange 2 year disease free survival to avoid severe breast symptoms. Younger patients (<50 years) assign higher importance to longer disease free survival.